Overview of tea constituents against type 2 diabetes - LU Peng; WANG Xiaochang; WANG Yingqi (浙江大学学报. 农业与生命科学版, 2016)
Type 2 diabetes mellitus (T2D) was a metabolic disorder, which was characterized by hyperglycemia in the context of insulin resistance and relative lack of insulin. The prevalence of T2D resulted in 90% of diabetic individuals suffering from it. In China, the percentage increased by 95%. The usage of anti-diabetic drug, however, could be associated with serious undesirable side effects, the most commonly observed are being hypoglycemia, mass gain, and gastrointestinal disturbances. Thus, it was necessary to find ant-i diabetic therapies that are not only safe and effective in controlling blood glucose levels, but also without serious side effects. Tea was a kind of natural ant-i diabetic material and had been studied for a long time because it was abundant in polyphenol. Previous studies mainly focused on type 1 diabetes mellitus (T1D), but recently, research about anti-T2D increased. At present, three main approaches of remedies could be concluded from the global researches.Glucose concentration in the body was directly influenced by insulin, so that insulin approach was one of the main therapies to treat T2D. Numerous reports showed that tea extracts could enhance insulin properties which could be subdivided into the amelioration of insulin resistance, improvement of insulin sensitivity and stimulation of incretin in cell or animal models. In detail, studies showed that tea extracts, especially epigallocatechin gallate (EGCG) could inhibit protein tyrosine phosphates 1b (PTP1B) to enhance insulin sensitivity and relieve insulin resistance via inhibiting 11betahydroxysteroid dehydrogenase type 1 (11β-HSD1). Similar results were also found that unknown extracts from tea could alleviate insulin resistance or enhance insulin secretion by inhibiting dipeptidyl peptidase Ⅳ (DPP-Ⅳ).This kind of approach includes two remedies, enhancing glycolysis and inhibiting gluconeogenesis. In skeletal muscle and adipose cells, tea extracts, particularly EGCG, could analog the function of insulin to stimulate glucose transporter protein-4 (GLUT 4) and enhance AMP-activated protein kinase (AMPK) pathway or PI3K/Akt pathway to strengthen the usage of glucose. In hepatic cells, EGCG from tea, down-regulated the mRNA of phosphoenolpyruvate carboxylase (PEPCK) and up-regulated the mRNA of glucose-6-phosphatase (G6Pase) through enhancing calmodulin dependent protein kinase kinases-β(CaMKK-β) and AMPK pathway.Anti-oxidants have been proved to play a significant role in T2D and complications. Tea, as a natural anti-oxidant, could definitely scavenge free radicals. Studies have reported that it could prevent T2D and its complications through enhancing polyol pathway flux, increasing formation of advanced glycation end products (AGEs), increasing expression of the receptor for AGEs and its activating ligands, activation of protein kinase C isoforms, and overactivity of the hexosamine pathway.Additionally, tea polyphenols including EGCG could also keep the balance between nitric oxide (NO) and endothelin (ET-1) and inhibit 11β-HSD1 to prevent T2D from happening indirectly.As a kind of natural functional beverage, tea and its extracts would be totally tested on resistance to T2D and could be recommended for combined use with present antidiabetic drugs in the treatment of T2D in the future.